Solearhynchus kostylewi (Meyer, 1932) comb. nov. (Acanthocephala: Echinorhynchidae), A rare parasite of Solea solea (Pisces: Soleidae) in the Gemlik Bay, Sea of Marmara - Kvach Y.; Oğuz M.C. (Parasite, 2010)
Paracanthocephaloides kostylewi (Meyer, 1932), a rare parasite of the common sole Solea solea, previously placed in the Arhythmacanthidae, is transfered to the genus Solearhynchus de Buron & Maillard, 1985 of the family Echinorhynchidae as Solearhynchus kostylewi (Meyer, 1932) new comb., because its proboscis is armed by a single type of hooks, the posterior hook in each row is pinlike and with feebly developed root. The species is redescribed on the basis of newly collected material from the Gemlik Bay, Sea of Marmara. A key to the species of Solearhynchus is provided.